An Exploration into the Effect of IELTS Teachers’ Self-Efficacy on their Resilience through a Self-efficacy Teacher Training Workshop - مریم طالبی; نسیم شنگرفام; بهدخت مال امیری (Journal of Applied Linguistics)
AbstractThe resilience of teachers has arisen as a crucial issue in developing exceptional teaching and learning experiences. It is imperative to foster resilience, which entails the capacity to endure and overcome obstacles and challenges encountered during the teaching process. Additionally, research has demonstrated that the self-efficacy of instructors is pivotal in this regard. To investigate these features, this research aimed to inspect the role of International English Language Testing System (IELTS) teachers' resilience and self-efficacy. To this end, a total of 60 IELTS teachers were chosen from Oxford Language Center, Tehran, Iran thanks to the convenient sampling and they completed a self-efficacy scale, and a resilience scale and were assigned to experimental and control groups that the former were trained through self-efficacy workshop training course in Oxford IELTS center in Tehran, Iran. The findings of this study through running an Analysis of Covariance (ANCOVA) indicated a constructive effect of self-efficacy on IELTS teachers' resilience after the workshop training course (F (1,57) = 60.00, p = .000 < .01, partial eta squared = .513, representing a large effect size). Correspondingly, it was revealed through Pearson Product-Moment Correlation that there is a positive and significant correlation between IELTS teachers’ self-efficacy and resilience (r = .462, p = .01 < .05). This study helps IELTS teachers improve their resilience. In line with these findings, some implications were presented to language stakeholders to consider the role of teacher self-efficacy.